PERANAN PERJANJIAN KERJA DALAM MEWUJUDKAN TERLAKSANANYA HAK DAN KEWAJIBAN PARA PIHAK DALAM HUBUNGAN KETENAGAKERJAAN - Niru Anita Sinaga (JURNAL ILMIAH HUKUM DIRGANTARA, 2017)
Abstract :An employment agreement is one of the bases of the employment relationship that creates a bond or legal relationship for the parties, resulting in rights and obligations. With the employment agreement is expected to realize the rights and obligations of the parties fairly. But in practice has not been fully realized. To make it happen, among others: With government intervention, this is in accordance with the characteristic of labor law in Indonesia which is mixture that is private and also public. In addition, the principles contained in the employment agreement must be in harmony with all principles contained in the law of contract, among others: Principle of freedom of contract, the principle of consensualism, the principle of legal certainty, the principle of good faith, the principle of personality, the principle of trust, the principle of equality Law, the principle of equilibrium, the principle of legal certainty, the moral principle, the principle of propriety and the principle of protection. These whole principles are interrelated to each others, inseparable, concurrent, proportionate and fair, and serve as a binding frame of the contents of the employment agreement. Keywords: Employment Agreement, Employment Relations Abstract :Perjanjian kerja merupakan salah satu dasar hubungan ketenagakerjaan yang menimbulkan perikatan atau hubungan hukum bagi para pihak, melahirkan hak dan kewajiban. Dengan adanya perjanjian kerja diharapkan dapat mewujudkan terlaksananya hak dan kewajiban para pihak dengan adil. Namun dalam prakteknya belum sepenuhnya terwujud.  Untuk mewujudkannya, antara lain: Dengan intervensi pemerintah, hal ini sesuai dengan kharakteristik hukum ketenagakerjaan di Indonesia yang bersifat campuran yaitu bersifat privat dan juga bersifat publik. Selain itu prinsip-prinsip yang terdapat pada perjanjian kerja harus memiliki keselarasan dengan seluruh prinsip-prinsip yang terdapat pada hukum perjanjian, antara lain: Asas kebebasan berkontrak, asas konsensualisme, asas kepastian hukum, asas itikad baik, asas kepribadian, asas kepercayaan, asas persamaan hukum, asas keseimbangan, asas kepastian hukum, asas moral, asas kepatutan dan asas perlindungan. Keseluruhan prinsip ini saling berkaitan satu dengan yang lainnya, tidak dapat dipisah-pisahkan, diterapkan secara bersamaan, berlangsung secara proporsional dan adil, dan dijadikan sebagai bingkai mengikat isi perjanjian kerja tersebut. Kata kunci: Perjanjian Kerja, Hubungan Ketenagakerjaan